Impact of Thermal Pulsation Treatment on Astigmatism Management and Outcomes in Meibomian Gland Dysfunction Patients Undergoing Cataract Surgery - Matossian C (Dove Medical Press, 2020)
Cynthia Matossian Matossian Eye Associates, Pennington, NJ, USACorrespondence: Cynthia MatossianMatossian Eye Associates, Two Capital Way, Ste 326, Pennington, NJ 08534, USATel +1 609-882-8833Fax +1 609-882-0077Email cmatossian@matossianeye.comPurpose: This study aimed to assess the effects of thermal pulsation system (TPS) treatment on astigmatism management in meibomian gland dysfunction (MGD) patients undergoing cataract surgery.Patients and Methods: This single-center pilot study included 25 eyes of 23 patients who had visually significant cataract and concomitant MGD-associated dry eye in at least 1 eye and were willing to undergo TPS treatment and wait for at least 6 weeks for tear film stabilization prior to cataract surgery. Post-TPS keratometric readings were used for presurgical planning, and the actual postoperative residual refractive astigmatism (RRA) was recorded. Pre-TPS keratometry was used to mathematically simulate the RRA that would have been obtained from the lens choice and astigmatism management without TPS treatment.Results: Following TPS treatment, the magnitude of astigmatism increased in 52% of eyes, decreased in 24%, and remained unchanged in 24%. Correspondingly, astigmatism treatment modality changed in 68% of eyes after tear film stabilization with TPS treatment. The type of astigmatism management increased (ie, shifted from no treatment to LRI or LRI to toric IOL) in 25% of eyes and decreased in 8%. Actual RRA ≤ 0.5 D was achieved in 76% of eyes, compared to simulated RRA ≤ 0.5 D in 40% of eyes (p=0.004).Conclusion: Stabilization of the tear film with TPS treatment resulted in less RRA than if pre-TPS keratometric readings had been used to determine the astigmatism management method and toric IOL power and axis.Keywords: dry eye cataract, meibomian gland dysfunction cataract, thermal pulsation treatment dry eye, astigmatism treatment cataract dry eye